Assessment contributions of physicochemical properties and bacterial community to mitigate the bioavailability of heavy metals during composting based on structural equation models. (October 2019) - Chen, Xiaomeng; Zhao, Yue; Zeng, Cici; Li, Yingjun; Zhu, Longji; Wu, Junqiu; Chen, Jian; Wei, Zimin
Graphical abstract: Highlights: Compost plays a positive role in mitigating the bioavailability of heavy metals. Organic matters and temperature are driving factors in beef cattle manures. Physicochemical property and bacterial community are primary in chicken manures. The bioavailability will be mitigated precisely according to deactivation pathways. Abstract: The aim of this study was to explore the pathways to mitigate the bioavailability of heavy metals (HM) during chicken and beef cattle manures composting. For raw materials, HM contents in animal manures from breeding farm were 1.5–3 times as much as that of domestic animal manures. Structural equation models (SEMs) based on denaturing gradient gel electrophoresis (DGGE) showed that mitigating bioavailability of HM was mainly attributed to physicochemical properties (organic matters content and temperature) during beef cattle manures composting. However, both physicochemical properties (organic matters content, temperature, pH and moisture) and bacterial community were critical factors during chicken manures composting. Furthermore, the statistical analysis from high-throughput sequencing verified the results of SEMs. Therefore, the bioavailability of HM will be mitigated by different deactivation pathways according to diverse raw materials composting.